GIS-material for the archaeological project: Stone Age remains in Fläskbergen - Local plan for recycling centre - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to local planning concerning a recycling centre within the property Lösings häradsallmänning, Krokek parish, Norrköping municipality, the Swedish National Heritage Board's Contract Archaeology Division, UV Öst has performed an archaeological assessment in the area. Great amounts of worked quartz, quartzite and other kinds of rock were found, as well as hammer stones, grindstones and anvil stones, particularly along what was once the Stone Age shore, about 50 m above sea level. To the north-west, by a Stone Age bay, the centre of the settlement was identified. The settlement is preliminarily dated to the Mesolithic and has got the temporary registration number UV 3, Krokek parish.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the assessment was to determine whether any archaeological remains were going to be affected by the development works, and if so, to delimit the area containing any remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför detaljplanering för en återvinningscentral i Krokeks socken, Norrköpings kommun, inom fastigheten Lösings häradsallmänning, utförde Riksantikvarieämbetet UV Öst en arkeologisk utredning i området. Vid utredningen hittades rikligt med bearbetad kvarts, kvartsit och bergart samt knack-, slip- och städstenar, framförallt i anslutning till ett i terrängen synligt forntida strandhak på omkring 50 m.ö.h. I nordväst har en forntida vik gått in och här återfinns boplatsens centrum. Boplatsen kan preliminärt dateras till mesolitikum och har fått den temporära beteckningen UV 3 (Krokeks sn).

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med utredningen var att avgöra om lagskyddad fornlämning berördes av exploateringsprojektet och om så var fallet att avgränsa de ytor som berördes av fornlämningen.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Stenålder i Fläskbergen - Detaljplan för återvinningsstation
Keywords: stone age; stenålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive